Academic Entrepreneurship for Social Innovation in Taiwan: The Cases of the OurCityLove Platform and the Forest App. (November 2019) - Wong, Chan-Yuan; Hsieh, Ying-Che; Wu, Ching-Yan; Hu, Mei-Chih
This study attempts to extend the definition of social innovation within the context of academic entrepreneurship. We consider how academic entrepreneurs can undertake commercial activities, and which ones, and how these activities contribute to the contexts of social innovation. We explore two cases that are derived from two premier universities in Taiwan in terms of research and academic entrepreneurship: OurCityLove from National Chiao Tung University (NCTU) and the Forest app from National Tsing Hua University (NTHU). The two cases show how social enterprises achieved the financial ability to expand their businesses and create the desired social values. While the first case, derived from NCTU, focused on providing useful information on social spaces, and services for the elderly, parents traveling with babies and those with disabilities (and also creating job opportunities for the latter), the other from NTHU created an app to influence those addicted to playing with their smartphones. The cases illustrate how the two universities capitalised on their technological competencies and academic programmes to support graduates and researchers in venturing into social entrepreneurship.